SOCIAL WORK PROFESSION: MAPPING CONTEMPORARY STATE OF PROFESSION - Verma, Jitendra Kumar; Patel, Shweta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
From the very beginning of human civilization, varied problems have been and are being faced by society. Poverty, unemployment, destitution, disaster, disease, displacement etc. are some global problems. These problems generate when human beings fail to properly adjust to and interact with their environment. Every society tries to mitigate these problems, so that people may lead a happy and healthy life. Social Work is a profession which is based on humanitarian and democratic philosophy. As per the global definition of Social Work, it is a practice-based profession and an academic discipline and social work profession promotes social change, social cohesion, and the development & empowerment for the wellbeing of people. The paper is based on secondary data and discusses manor issues and state of Social Work profession in contemporary era.